Determinant Factors on Intentions to Purchase Imported Food Products with Halal Labels - Nanah Sujanah; Jakaria Jakaria; Najmudin Najmudin (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This research aims to determine the influence of country of origin on intentions to purchase imported food products labeled halal and the influence of halal awareness on intentions to purchase imported food products labeled halal. The method used in this research is descriptive quantitative, with a population of the entire Serang City community. The sampling technique uses Ferdinand's theory, multiplying the overall indicators of all variables by a number between 5 and 10, based on the calculation results, a total of 110 samples/respondents for this research are obtained. The data collection technique uses a questionnaire. Data were processed using Smart PLS 3.2.9 software and analyzed using the structural equation modeling (SEM) method with a partial least squares (PLS) approach. The results of this research show that the Country of origin has a significant positive effect on the intention to purchase imported food products labeled halal. Halal awareness has a significant positive effect on the intention to purchase imported food products labeled halal.